Does Proprioceptive Neuromuscular Facilitation-Based Hamstring Stretching Influence Deep Cervical Flexor Muscle Endurance? - Altay Kosova; Omer Osman Pala (Life, 2025)
Aim: To assess the acute effects of proprioceptive neuromuscular facilitation (PNF), stretching was applied to the hamstring muscles to evaluate deep cervical flexor endurance. Potential variables correlating with endurance adaptations were examined. Methods: This randomized controlled trial performed between September 2023 and June 2024 included healthy female university students aged 18–25 years. Participants were randomly assigned to either the control or the PNF group. Variables included age, height, weight, body mass index, Beighton score, hamstring flexibility, and deep cervical flexor muscle endurance; correlations between changes in hamstring flexibility and DCF endurance were explored. Hamstring flexibility was assessed using the Passive Knee Extension Test, and deep cervical flexor endurance was assessed using the Cranio-Cervical Flexion Test. The PNF group received hold–relax exercises while controls did not receive any intervention. Results: The study included 32 control participants and 32 individuals in the PNF group. The PNF group was marginally but significantly older than the control group [22 (21–23) vs. 21 (21–22); p = 0.038]. At baseline, the PNF group showed greater hamstring flexibility (p = 0.010). Both groups showed significant improvements in hamstring flexibility (p < 0.001 for both), but the improvement in the PNF recipients was far greater (p < 0.001). Regarding deep neck flexor endurance, no significant difference was observed between the groups at baseline (p = 0.958) or in final measurements (p = 0.244), although both groups showed significant improvements from baseline (p < 0.001 for both). There were no significant correlations between the change in deep neck flexor endurance and any of the examined variables. Conclusions: Our study found that a single session of PNF stretching significantly improved hamstring flexibility but did not immediately enhance deep neck flexor endurance. This emphasizes the need for further research into longer-term interventions to assess whether interventions on hamstring flexibility can improve cervical function.